Effectiveness of Voriconazole in Treating Fungal Keratitis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Aryati, Yulia Ayu; Idrus, Elfa Ali (MPI (Media Pharmaceutica Indonesiana), 2022)
Antifungal intervention fails in approximately half of fungal keratitis patients, demonstrating its limitations. Voriconazole use for fungal keratitis has raised new interest because of its broad spectrum and good ocular penetration. However, its effectiveness has not been systematically evaluated. Here we try to clarify the benefits of voriconazole in fungal keratitis cases. Randomized controlled trials (RCTs) comparing voriconazole to placebo or other antifungal medications for fungal keratitis were searched in several databases, including PubMed, Scopus, Cochrane Library, ClinicalTrials, and WHO-ICTRP. The primary outcome that analyzed was best spectacle-corrected vision acuity (BSCVA). The secondary outcomes were treatment success, corneal perforation or need for therapeutic penetrating keratoplasty (TPK). From 621 records, nine studies were selected for analysis. The results were as follows: As an initial therapy, topical natamycin outperformed voriconazole in BSCVA (mean difference = 0.14; 95% CI 0.02 to 0.26; P =.03). Voriconazole also has a greater risk of corneal perforation or TPK than natamycin (RR=1.69; 95% CI 1.11 to 2.58; P=.02). As an adjuvant, there is no significant difference found in BSCVA, treatment success, event of corneal perforation, or need for TPK between voriconazole and the other antifungal agents (itraconazole, ketoconazole, amphotericin B, natamycin, and placebo). This study shows that voriconazole is less superior than natamycin in treating early infections of fungal keratitis. More RCTs with larger samples are needed to evaluate voriconazole's adjuvant efficacy.